Assessing antixenosis of soybean entries against Piezodorus guildinii (Hemiptera: Pentatomidae) - Silva, Jose P. G. F. [UNESP]; Baldin, Edson L. L. [UNESP]; Canassa, Vinicius F. [UNESP]; Souza, Efrain S. [UNESP]; Lourencao, Andre L. (Springer, 2014)
Piezodorus guildinii (Westwood) (Hemiptera: Pentatomidae) is a major soybean (Glycine max (L.) Merrill) pest and reduces grain quality and yield worldwide. In the context of integrated pest management strategies, plant resistance stands out as an extremely valuable tool for the management of pest populations. Here, we evaluated the resistance of several soybean entries to P. guildinii using tests of attractiveness and feeding preference. We also evaluated trichome number and length as well as pod hardness to evaluate the relationships between these parameters and the resistance to stink bug. D 75-10169, PI 171451, PI 229358, PI 227687, IAC 100, IAC 78-2318, PI 274454, PI 274453 and IAC 19 were less attractive and less consumed by stink bugs. D 75-10169, PI 227687 and PI 274454 received low probe numbers and a short consumption duration per probe; IAC 100 and PI 274453 received low probe numbers; PI 171451 and PI 229358 received short probe durations; and IAC 19 received the highest number of probes. There was no correlation between trichome density and length with the attractiveness and feeding preference of the adult insects; however, pod hardness results suggested that this morphological factor may influence the number of probes performed by the insect. PI's entries, D 75-10169, IAC 100 and IAC 19 expressed antixenosis resistance and should be appropriate for use in soybean breeding programs aimed at developing entries with higher resistance to pest insects.
Keywords: Host plant resistance; Redbanded stink bug; Feeding preference; Attractiveness